Heirloom or Antique? Import or Imitation? Objects with Fictive “Biographies” in Early Iron Age Knossos - Antoniadis, Vyron (Tekmeria, 2021)
During the Early Iron Age, Knossos was one of the most important cities of the Aegean. In addition to objects from elsewhere in the Aegean, a wide range of Cypriot, Phoenician and North Syrian imports has been discovered in the Early Iron Age Knossian cemeteries. In certain cases, these grave goods predate their funerary context by a century. This paper examines the stylistic and contextual dating of these imports, in an attempt to associate, from a contextual point of view, these items with the funerary practices of the Knossians. Grave goods deposited in the same cemeteriesalso included Early Iron Age local imitations of Late Bronze Age Near Eastern imports. It is suggested that members of the Early Iron Age Knossian elite treated certain contemporary objects, which belonged stylistically either to the Late Bronze Age Cypriot, Phoenician or North Syrian traditions, on the one hand, or to the local Minoan tradition, on the other hand, as if they were antiques and/or heirlooms. In this way, that is, by appropriating the ancestral past of the community, the elite could establish and maintain their authority. For this reason, “fake” keimelia and heirlooms had to acquire new complex “biographies”.